Involvement of the skin during bluetongue virus infection and replication in the ruminant host - Darpel, Karin E; Monaghan, Paul; Simpson, Jennifer; Anthony, Simon J; Veronesi, Eva; Brooks, Harriet W; Elliott, Heather; Brownlie, Joe; Takamatsu, Haru-Hisa; Mellor, Philip S; Mertens, Peter PC (Veterinary research (Paris), 2012)
Bluetongue virus (BTV) is a double stranded (ds) RNA virus (genus Orbivirus; family Reoviridae), which is considered capable of infecting all species of domestic and wild ruminants, although clinical signs are seen mostly in sheep. BTV is arthropod-borne ("arbovirus") and able to productively infect and replicate in many different cell types of both insects and mammalian hosts. Although the organ and cellular tropism of BTV in ruminants has been the subject of several studies, many aspects of its pathogenesis are still poorly understood, partly because of inherent problems in distinguishing between "virus replication" and "virus presence".BTV replication and organ tropism were studied in a wide range of infected sheep tissues, by immuno-fluorescence-labeling of non-structural or structural proteins (NS2 or VP7 and core proteins, respectively) using confocal microscopy to distinguish between virus presence and replication. These results are compared to gross and microscopic pathological findings in selected organs from infected sheep. Replication was demonstrated in two major cell types: vascular endothelial cells, and agranular leukocytes which morphologically resemble lymphocytes, monocytes/macrophages and/or dendritic cells. Two organs (the skin and tonsils) were shown to support relatively high levels of BTV replication, although they have not previously been proposed as important replication sites during BTV infection. The high level of BTV replication in the skin is thought to be of major significance for the pathogenesis and transmission of BTV (via biting insects) and a refinement of our current model of BTV pathogenesis is discussed.